Algebraic L2-decay of weak solutions to the magneto-hydrodynamic equations. (December 2019) - Liu, Zhaoxia
Abstract: We consider the asymptotic behavior of weak solutions to the incompressible magneto-hydrodynamics (MHD) equations in the whole space R n, n ≥ 2 . The algebraic decay of the total energy of weak solutions to Cauchy problem of MHD equations is given by establishing an important inequality on weak solutions of MHD equations.